MEMPERSIAPKAN KETAHANAN KELUARGA SELAMA ADAPTASI KEBIASAAN BARU DI MASA PANDEMI COVID-19 - Maulana Rezi Ramadhana (Research Centre for Population, Indonesian Institute of Sciences, 2020)
Changes in family dynamics during the isolation period of COVID-19 have an impact on family resilience in preparing for the adaptation of new habits in Indonesia. This study examines emotional reactions and family resilience, using family demographic groups, namely family type, parent's occupational type, and a residential area used as study variables. The sample came from 318 overseas student families who had reunited with families from 23 cities and districts in West Java Province. Simple frequency data analysis were used to present related situations. The results of the study showed that family type, family socioeconomic (parents' occupation), and the type of residential area of the family showed differences in positive emotions, negative emotions and were significant to family resilience during COVID-19 isolation. The implications of this study lead to the function of families in strengthening family resilience to prepare for the adaptation of new habits in Indonesia.